2016
DOI: 10.1371/journal.pone.0150267
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric Amyloid Beta Peptide in Hexafluoroisopropanol Detected by Small Angle Neutron Scattering

Abstract: Small proteins like amyloid beta (Aβ) monomers are related to neurodegenerative disorders by aggregation to insoluble fibrils. Small angle neutron scattering (SANS) is a nondestructive method to observe the aggregation process in solution. We show that SANS is able to resolve monomers of small molecular weight like Aβ for aggregation studies. We examine Aβ monomers after prolonged storing in d-hexafluoroisopropanol (dHFIP) by using SANS and dynamic light scattering (DLS). We determined the radius of gyration f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 57 publications
3
32
0
Order By: Relevance
“…The Structure factor S(Q) equals 1 for low concentrations as in our case and the Form factor F(Q) depends on the shape and size of the scattering objects but not on the concentration. The data analysis was carried out by using a geometry independent Form factor known as the Becauge model [15,26]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Structure factor S(Q) equals 1 for low concentrations as in our case and the Form factor F(Q) depends on the shape and size of the scattering objects but not on the concentration. The data analysis was carried out by using a geometry independent Form factor known as the Becauge model [15,26]:…”
Section: Resultsmentioning
confidence: 99%
“…Instead, Zhang-Haagen et al showed that SANS is able to resolve monomers of small molecular weight such as Aβ in deuterated HFIP, of a radius of gyration of 1.0 ± 0.1 nm (in agreement with 3D NMR). [15] To evaluate the possibilities and limitations of SANS technique to observe size and conformational characteristics of Aβ, we evaluated Aβ 1−40 , the most common Aβ peptide, in disparate solvents. Since water (H 2 O or D 2 O buffers) can induce fast aggregation of monomer while DMSO can disaggregate Aβ oligomers/fibrils, we examined Aβ 1−40 monomeric solution in DMSO, and Aβ 1−40 oligomer and protofibril preparations in biological relevant environment (D 2 O buffers).…”
Section: Introductionmentioning
confidence: 99%
“…The Ab 42 monomer (1 mg) was resuspended in 1 ml of cold 1,1,1,3,3,3-hexauoro-2-propanol (HFIP), and it was kept in the dark for 30 min at 4 C to solubilize the peptide in the monomeric stage. 44,45 The solution was aliquoted (25 ml) and dried under vacuum in a rotary evaporator for 1 h at room temperature; the resultant transparent lm was stored at À80 C for further experiments. The amyloid brils were formed as previously described; 46 briey, the solubilized Ab 42 was dissolved in polymerization buffer containing PBS 1Â (nal concentration of 10 mM PO 4 3À , 137 mM NaCl, and 2.7 mM KCl) and 1% DMSO and incubated at 37 C at different time points.…”
Section: Preparation and Brillization Of Ab 42 Peptidementioning
confidence: 99%
“…Although this molecule is missing the Ile and Ala amino acid (41)(42) residues: the C-terminal part of the Aβ 42 fibril protein, does not make any essential difference in the structure and or in the conformation. [The hydropathy indices are: Ile = 4.5; Ala = 1.8 (23). ]…”
Section: The Aβ 42 Peptide Monomermentioning
confidence: 99%
“…The third team also studied this molecule by cryo-electron microscopy (22). On the other hand, a hairpin-like structure of the full-length Aβ 42 monomer was determined by NMR (18) and by small angle neutron scattering (23) in the presence of organic co-solvents (e.g. hexafluoroisopropanol), as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%